Development and validation of Hebrew version of the UCLA Scleroderma Clinical Trial Consortium Gastrointestinal Tract Instrument 2.0. Issue 1 (February 2023) - Ozeri, David; Peretz, Shani; Oppenheim, Amit; Watad, Abdallah; Lidar, Merav; Braun-Moscovici, Yolanda
Aim: The aim of this study was to test the reliability of the University of California, Los Angeles Scleroderma Clinical Trial Consortium Gastrointestinal Tract (UCLA SCTC GIT) 2.0 questionnaire in Hebrew. Methods: UCLA SCTC GIT 2.0 was translated into Hebrew using the translation–retranslation method. The Hebrew version of the UCLA SCTC GIT 2.0 and the Hebrew version of the Short Form 36 (SF-36) were administered to 19 Hebrew-speaking patients with systemic sclerosis. Internal reliability was assessed using Cronbach's alpha. The Hebrew questionnaire was then tested for external validity using Spearman's correlation coefficient. Correlations ( rho ) ⩽ 0.29 were considered small, 0.30 to 0.49 were moderate, and those ⩾0.50 were considered large. Differences were considered statistically significant at p < 0.05. Results: A group of 19 patients treated at Sheba Medical Center meeting the ACR/EULAR classification system for systemic sclerosis were included in the study. The mean age of the participants was 60.4 ± 12 years with a female predominance (84%). Diffuse cutaneous scleroderma accounted for 10 of the participants (54%), 7 had limited cutaneous scleroderma (36%) with 2 having an overlap syndrome (10%). The Cronbach's alpha value for the UCLA SCTC GIT 2.0 scale was 0.908 showing reliability. In addition, the UCLA SCTC GIT 2.0 showed correlation to the SF-36. Conclusion: The translation of the Hebrew UCLA SCTC GIT 2.0 scale was reliable and valid with a total Cronbach's alpha score among the participants of 0.908. Cronbach's alpha was particularly reliable in reflux, bloating, social function, and emotional well-being. Our results suggest that our Hebrew version of the UCLA SCTC GIT 2.0 scale can be used as a tool in future studies with Hebrew-speaking patients. In the abstract conclusion, it states that "Cronbach's alpha was particularly reliable in reflux, bloating, social function, and emotional well-being." The related data should be listed in the results section and then an interpretation of the results should be listed in the conclusions section. Please revise.